2003
DOI: 10.1080/1042819021000037976
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Flow Cytometry for Detection of Minimal Residual Disease in Acute Myeloid Leukemia

Abstract: The term minimal residual disease (MRD) describes the situation in which, after chemotherapy for acute leukemia (AL), a morphologically normal bone marrow (BM) can still harbor a relevant amount of residual malignant cells. Several techniques are now amenable to investigate MRD, and all together they have designated a new era in which a re-definition of the current criteria of complete remission (CR) is required. Depending upon the measured level of MRD we can distinguish a variety of clinical situations rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…13,[17][18][19]21,22,33,39,40 Drach et al 21 evaluated MRD in 68 patients with AML. In follow-up assessment of BM samples collected consecutively after induction therapy, they observed that only patients in whom a LAP continued to be detected experienced early relapse.…”
Section: Clinical Studies Of Mrd Investigation In Amlmentioning
confidence: 99%
“…13,[17][18][19]21,22,33,39,40 Drach et al 21 evaluated MRD in 68 patients with AML. In follow-up assessment of BM samples collected consecutively after induction therapy, they observed that only patients in whom a LAP continued to be detected experienced early relapse.…”
Section: Clinical Studies Of Mrd Investigation In Amlmentioning
confidence: 99%
“…Assessment of response to therapy (including “minimal residual disease” testing) and persistence of FCI‐detectable MRD following therapy, which is often an adverse prognostic factor. However, the optimal frequency of such monitoring has not been established (112, 137–163). Documentation of progression or relapse. Diagnosis of additional intercurrent hematolymphoid neoplasm, either treatment‐ related (such as MDS/AML or PTLD) or coincidental (164–170).…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…Patients were classified in three risk groups for cytogenetic abnormalities according to Grimwade et al (22). Favorable risk was defined by the presence of t(15;17) or t(8;21) or inv (16) and poor risk was defined by the presence of either five unrelated abnormalities, monosomy 5 or 7, abnormalities of the long arm of chromosome 5, or inv(3) (q21:q26). Patients who did not meet the criteria for poor or favorable risk were classified as intermediate risk.…”
Section: Patient Samplesmentioning
confidence: 99%
“…Although studies of MRD detection by MFC in AML are still limited when compared with acute lymphoblastic leukemia (ALL) (11)(12)(13)(14), several reports have been published providing evidence that study of MRD are a useful tool for predicting relapse (8)(9)(10)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%